Material Development for Informatics Management Students Based on Inquiry-Based Language Learning - Purbasari, Dita Anggi; Ayu Kusuma Asri, Anindhiasti (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
The research was aimed at (1) finding out the quality of the existing textbook used to teach English to the second-semester students of the Informatics Management program, (2) finding out the students’ needs, and (3) developing an English textbook for second-semester students of Informatics Management major based on inquiry-based language learning (I.B.L.L.). It was a research and development (R & D) study to supplement the textbook for Informatics Management students using I.B.L.L. R & D study had two stages: (1) the exploration stage, which consists of library research, document analysis, and needs analysis and (2) the development stage, which was aimed at designing the supplementary textbook. The data were analyzed by using an interactive method. The result showed that the “English for Computer” textbook could be supplementary for Informatics Management students.